A Juridical Analysis of Mediation in the Resolution of Land Disputes Based on Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) Number 21 of 2020 - Muhammad Farid Hariyanto; Muhammad Islahuddin (CV Edujavare Publishing, 2026)
Land disputes remain a recurring legal issue in Indonesia and require effective resolution mechanisms that promote peaceful settlement while ensuring legal certainty for the parties involved. One available mechanism is mediation, as regulated under Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (ATR/BPN) Number 21 of 2020 concerning the Handling and Resolution of Land Cases. This study aims to analyze the legal framework governing mediation in land dispute resolution under the regulation and to assess the extent to which it provides legal certainty for disputing parties. This research employs a normative juridical method using a statutory and conceptual approach. Primary, secondary, and tertiary legal materials were collected through library research and analyzed qualitatively using a deductive approach. The findings indicate that Regulation Number 21 of 2020 clearly regulates the position of mediation, the parties involved, the mediator, mediation procedures, and the legal consequences of mediation outcomes. The regulation also reflects key principles of Alternative Dispute Resolution, including voluntariness, deliberation, party participation, mediator neutrality, and consensus-based settlement. Therefore, the regulation provides a clear legal framework that supports legal certainty and encourages effective and peaceful resolution of land disputes.